ANALISIS LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Eddy Mulyadi Soepardi (MAGMA : JURNAL MAGISTER MANAJEMEN, 2014)
This study aimed to analyze the effect of Liquidity and Leverage on Profitability food and beverage companies listed on the Indonesia Stock Exchange. Samples in this study as many as 12 companies. Sampling in this study using purposive sampling. Data were analyzed using regression analysis. The results showed that: First, variable liquidity (current ratio) has a 0.01 probability value 0.05. Thus the current ratio (CR) significant effect on profitability (Return On Assets) at 95% confidence level. CR positive effect on ROA with a coefficient of 1.022.Second, the variable Leverage (Debt Assets Ratio) had a probability value 0.931 0.05. Thus Debt Assets Ratio (DAR) had no significant effect on profitability (Return On Assets). Increasing the value of DAR does not significantly affect the increase in the value of ROA.Third, the F value of 9.158 at F Prob value of 0.000 0.05. So that CR and DAR jointly significant effect on ROA. Thus simultaneous hypothesis variables CR and DAR together positive and significant impact on ROA.